2003
DOI: 10.1111/j.1745-6592.2003.tb00672.x
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of Unsaturated Flow in Wastewater Soil Absorption Systems

Abstract: It is common practice in the United States to use wastewater soil absorption systems (WSAS) to treat domestic wastewater. WSAS are expected to provide efficient, long‐term removal of wastewater contaminants prior to ground water recharge. Soil clogging at the infiltrative surface of WSAS occurs due to the accumulation of suspended solids, organic matter, and chemical precipitates during continued wastewater infiltration. This clogging zone (CZ) creates an impedance to flow, restricting the hydraulic conductivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 13 publications
6
33
0
Order By: Relevance
“…They also developed a one-dimensional finite element model to simulate the flow and solute transport in an unsaturated zone. The effect of biomat layer on the hydraulic properties within the unsaturated zone of soil absorption system was investigated by Beach and McCray (2003). Rockhold et al (2005) examined experimentally and numerically the effect of bacterial growth on the hydraulic properties of unsaturated soils.…”
Section: Introductionmentioning
confidence: 99%
“…They also developed a one-dimensional finite element model to simulate the flow and solute transport in an unsaturated zone. The effect of biomat layer on the hydraulic properties within the unsaturated zone of soil absorption system was investigated by Beach and McCray (2003). Rockhold et al (2005) examined experimentally and numerically the effect of bacterial growth on the hydraulic properties of unsaturated soils.…”
Section: Introductionmentioning
confidence: 99%
“…Results were checked by running the same input parameters in SWIM v1.0 (Ross 1990). Biomat resistances used in the model encompassed a range of values reported in the literature Beach and McCray 2003). The FLUX model, in accordance with assumptions held for Eqn 1, assumed that all flow was steady-state with a unit gradient, and flow occurred in a 1-directional manner, vertically through the biomat zone.…”
Section: One-dimensional Modellingmentioning
confidence: 99%
“…3) is hypothesised to be an important absorption pathway for effluent under situations of peak loading. There are a limited number of studies modelling unsaturated flow in SAS (Janni et al 1980;Hansen and Mansell 1986;Beach and McCray 2003;Radcliffe et al 2005), but the specific partitioning of biomat zone and nonbiomat zone flow in SAS is not widely reported. A study by Brouwer et al (1979) found flow through the sidewall to be greater than bottom flow in some duplex soils in Victoria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The area over which the effluent is distributed is a major determinant of overall contaminant attenuation and the achievement of treatment objectives. Modeling studies in the literature have largely assumed biomat hydraulic properties are given, and used numerical simulation packages such as HYDRUS2D (Šimůnek et al 2011) and its reactive transport modules (CW2D (Langergraber and Šimůnek 2005) and CWM1 (Langergraber et al 2009)) to investigate varying hydraulic régimes and compare open and gravel IS architectures in a 2D plane perpendicular to the trench (Huntzinger Beach and McCray 2003;Radcliffe et al 2005;Finch et al 2008;Beal et al 2008;Wunsch et al 2009). Our approach differs in proposing a minimal analytical model to describe the biomat development along the IS by coupling the flow and transport with biomass growth, which we then investigate through analytical approximations.…”
Section: Introductionmentioning
confidence: 99%